2010
DOI: 10.1002/ccd.22731
|View full text |Cite
|
Sign up to set email alerts
|

Physiological assessment of renal artery stenosis: Comparisons of resting with hyperemic renal pressure measurements

Abstract: Renin production, an index of renal ischemia, was markedly greater at hyperemia than at rest, suggesting that RAS, with either an HSG of 21 mm Hg or a renal FFR of 0.90, can be considered a hemodynamically significant stenosis. Intrarenal papaverine neither prolonged the QT interval nor induced ventricular arrhythmias and the safety of which will need to be corroborated in a large study. © 2010 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…The new finding in the report of Kapoor et al [3] besides reproducing the findings of De Bruyne et al [4] is the effect of intra renal papaverine on the ECG. Intracoronary papaverine is no longer used for coronary hyperemia because of QT prolongation and Torsade de Pointe but as Kapoor et al [3] demonstrated it has no electrocardiographic effects when given intrarenally likely due to the dilution effect before the drug reaches the heart.…”
mentioning
confidence: 50%
See 4 more Smart Citations
“…The new finding in the report of Kapoor et al [3] besides reproducing the findings of De Bruyne et al [4] is the effect of intra renal papaverine on the ECG. Intracoronary papaverine is no longer used for coronary hyperemia because of QT prolongation and Torsade de Pointe but as Kapoor et al [3] demonstrated it has no electrocardiographic effects when given intrarenally likely due to the dilution effect before the drug reaches the heart.…”
mentioning
confidence: 50%
“…Nonetheless, the application of a measurable endpoint of significant renal artery pathophysiology is preferable to prior statements on what constituted a significant narrowing. Despite the use of different hyperemic agents, both studies [3,4] had similar renal FFR cut points suggesting reduced blood pressure and maintained or improved renal function should follow stenting of these lesions. Long-term clinical correlations validating this postulated benefit are underway.…”
mentioning
confidence: 85%
See 3 more Smart Citations